PENGARUH PERASAAN ANAK PENGHAFAL AL-QUR’AN TERHADAP IKATAN PERSAHABATAN DI YAYASAN TAHFIDZ AR-RAIHAN JEMBER - Noor Ikhsan Silviantoro; Abd.Muthalib; Muhammad Yassir (Al-Majaalis : Jurnal Dirasat Islamiyah, 2024)
This study examines the impact of children's feelings on friendship ties in the context of memorizing the Qur'an at the Tahfidz Ar-Raihan Foundation in Jember. Using a quantitative approach, data were collected through a Likert scale questionnaire and analyzed using simple linear regression. The validity and reliability of the questionnaire were confirmed with all items showing significance values ​​below 5% and Cronbach's Alpha values ​​within the acceptable range (0.708 for children's emotions and 0.746 for friendship ties). The analysis showed a significant positive relationship between children's emotional states and their friendship ties, with 35.1% of the variation in friendship ties explained by children's emotions. These findings highlight the importance of emotional well-being in the social dynamics of Qur'an education, emphasizing the need for an emotionally supportive environment to enhance learning and social interaction among children memorizing the Qur'an. Further research is recommended to explore additional factors influencing this relationship in order to develop more comprehensive educational strategies.